2005
DOI: 10.1111/j.1540-8191.2005.200485.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Incomplete Left Ventricular Mass Regression Following Aortic Valve Replacement for Aortic Stenosis

Abstract: Measures of valve hemodynamics were not important predictors of incomplete regression of hypertrophy. The extent of preoperative hypertrophy was the most important predictor, suggesting that earlier surgical intervention may reduce the extent of hypertrophy postoperatively. Furthermore, the significance of LV hypertrophy to long-term survival must be reassessed, in the absence of scientific evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
38
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 23 publications
1
38
1
Order By: Relevance
“…These findings indicate that irreversibility or, at best, partial reversibility of both myocardial dysfunction and hypertrophy may already be present prior to aortic valve replacement. Other investigators have also observed partial reversibility of ventricular hypertrophy and dysfunction following aortic valve replacement in AR [5,14] as well as AS patients [15]. The present results extend those of previous studies, and also provide new data showing that preoperative LV mass (!200% of normal) is strongly associated with persistent postoperative hypertrophy and persistent postoperative contractile dysfunction.…”
Section: Discussionsupporting
confidence: 89%
“…These findings indicate that irreversibility or, at best, partial reversibility of both myocardial dysfunction and hypertrophy may already be present prior to aortic valve replacement. Other investigators have also observed partial reversibility of ventricular hypertrophy and dysfunction following aortic valve replacement in AR [5,14] as well as AS patients [15]. The present results extend those of previous studies, and also provide new data showing that preoperative LV mass (!200% of normal) is strongly associated with persistent postoperative hypertrophy and persistent postoperative contractile dysfunction.…”
Section: Discussionsupporting
confidence: 89%
“…There is a large body of evidence showing that PPM after SAVR negatively affects survival,9 left ventricular remodelling,10 exercise capacity11 and quality of life 12. It is largely concluded that elevated gradients can be held responsible for the negative effects of PPM.…”
Section: Discussionmentioning
confidence: 99%
“…21 In addition, measures of prosthetic hemodynamics may not affect the degree of LV mass regression after SAVR, with only pre-operative LV hypertrophy demonstrated as a significant predictor. 22,23 Reduced LVEDD was likely a large factor for reduced LV mass after SAVR in previous studies. However, new data suggests that the type of prosthesis can affect the degree of LV mass regression and survival.…”
Section: Discussionmentioning
confidence: 99%